Functional genomics and dynamic assembly of cuticular proteins analogous to peritrophins and Knickkopf into the procuticle of Tribolium castaneum - Li, Beibei (Kansas State University, 2014)
The exoskeleton of insects, the cuticle, functions as a support structure and a physical barrier that protects insects from mechanical damage and dehydration. The exoskeleton is mainly made of chitin and proteins, some cross-linked to one another into certain patterns to form the rigid and resistant cuticle. In previous studies from our laboratory, cuticular proteins analogous to peritrophins (CPAPs) and Knickkopf (Knk) were identified and characterized mainly at the pharate adult stage during insect development. However, the dynamic assembly of both CPAP and Knk into the cuticle and the functions of the CPAPs are still not fully understood. Our study is to investigate how these cuticular proteins are assembled into the cuticle during different developmental stages and carry out their functional characterizations in the red flour beetle, Tribolium castaneum. RNA interference (RNAi) experiments that resulted in down-regulation of transcripts for CPAP 1-C, CPAP1-H, CPAP 1-J, CPAP 3-C and Knk genes resulted in molting defects. Confocal and transmission electron microscopic analysis examined protein expression at twelve stages of development, as well as the span from young larva through adult day 3 stages. The results suggested that the CPAP 3-C protein is present in the lower part of endocuticle in the so-called assembly zone and it was not distributed thoughout the procuticle with chitin. Down-regulation of CPAP 3-C transcripts revealed a disorganized assembly zone; however, no loss of chitin content or the laminar architecture of the procuticle was found. Knk protein was present throughout the procuticle and some of the protein was found inside of the epithelial cells.
Keywords: Cuticular proteins; Tribolium castaneum; Entomology (0353)